'Pitstop of Death': Irish newspaper coverage of Iraq war protests at Shannon airport*. Issue 1 (2nd January 2019) - Browne, Harry; Coulter, Colin; Flynn, Roddy; Hetherington, Vanessa; Titley, Gavan
ABSTRACT: The airport at Shannon, County Clare, in the west of Ireland, has been a strategically important US military stopping-point in the wars of the twenty-first century and consequently has at times become a focal point for the various forms of protest that have been adopted by the Irish peace movement. This study, drawing upon a database of Irish national newspaper articles dealing with the anti-war movement from September 2002 to May 2003 – a period covering the build-up to the invasion of Iraq to its immediate aftermath – examines how the US military's use of Shannon and the protests against it were framed in the print media. The focus on Shannon made Irish media coverage different from that in other European countries: the authors find that a period of Irish government equivocation about the military significance of the airport permitted campaigners to attract some sympathetic attention by providing information about troop movements there – successfully promulgating a 'counterframe', i.e. a news frame that ran counter to the government line – but that as the war approached this gave way to a newspaper focus on the dangers of protest, including the ascription of violence.